Investigation of broadband 1.8 μm luminescence in Tm3+ activated gallium tellurite glass with high quantum efficiency. (1st May 2023) - Zhang, Chi; Han, Kexuan; Wu, Tong; Zhou, Dechun; Wang, Shunbin; Liu, Mo
Abstract: In this study, Tm 3+ -doped gallium tellurite glass samples were fabricated in order to achieve the fluorescence emission at 1.8 μm. Firstly, the optical properties (such as dispersion, absorption and fluorescence curves) of the glass samples were investigated and discussed. Meanwhile, the nonlinear refractive index, Judd-Ofelt (J-O) parameters, effective fluorescence bandwidth, absorption and emission cross sections, as well as gain coefficient of the glass samples were estimated in detail utilizing the collected data. Subsequently, lifetime evaluation was undertaken to explore the fluorescence decay behavior of Tm 3+ at the 3 F4 energy level. The approach to in-depth analysis of the energy transfer process between Tm 3+ was carried out by the quantitative calculations. Notably, we found that the quantum efficiency of the GT-0.75 sample was as high as 73.5% under the action of the 808 nm laser diode. Lastly, the thermal characteristics and internal structural units of the glass samples were depicted by the DSC curves, Raman and FTIR spectra. The present results indicate that Tm 3+ -doped gallium tellurite glass is a kind of laser glass material with great potential in 1.8 μm wavelength band.